Ants in Our P.A.N.T.S: InvestiGators # 4 - Green, John Patrick (New York : First Second, 2021)
Mango is sent out on a mission to stop crime before it happens with RoboBrash, Brash's replacement while he recovers from their last mission, using S.U.I.T.'s newest method of crime-fighting called P.A.N.T.S. They soon discover the plans of an evil astronaut named Maestronaut involve giant ants, and it's up to the InvestiGators to save the day.
new kids book 2023 summer.
School Library Journal
2-5.
Accelerated Reader AR-ATOS
Keywords: Alligators -- Fiction; Cartoons and comics; Private investigators -- Fiction; Graphic novels